Postacie kobiece Starego Testamentu w alegorycznej egzegezie Orygenesa - Szram, Mariusz (Vox Patrum, 2016)
The article systematises the metaphors ascribed by Origen (185-253/254) to the well-known female characters of the Old Testament utilising the method of allegorical exegesis of the text of Scripture. Females appearing on the pages of the historical books of Bible are – according to the Alexandrian – allegories of human virtues or defects. They embody the spiritual warfare between the spirit and the body, between the mind and the feelings. In the collective sense they symbolize the synagogue or the church chosen from the Gentiles, and in the individual sense – the human soul in its relation to God. Origen refers to the telling names of women, translating them and embedding into the spiritual context often giving the several different allegorical meanings to the same biblical person. Despite the often-quoted in his writings beliefs characteristic to the ancient world, proclaiming that the woman is a symbol of bodily feelings and the man – a symbol of the intellectual abilities, majority of allegorical interpretations relating to the Old Testament women indicates a personification of the virtues worthy of imitation. This phenomenon is conditioned with the meaning of the names of those persons and the role attributed to them by the biblical authors, but Origen’s interpretations are original and based on his own concept of spiritual life. They deny opinions of misogyny of Origen and the early Christian writers in general.